2012
DOI: 10.1038/leu.2012.222
|View full text |Cite
|
Sign up to set email alerts
|

Gab2 signaling in chronic myeloid leukemia cells confers resistance to multiple Bcr-Abl inhibitors

Abstract: Grb2-associated binder 2 (Gab2) serves as a critical amplifier in the signaling network of Bcr-Abl, the driver of chronic myeloid leukemia (CML). Despite the success of tyrosine kinase inhibitors (TKIs) in CML treatment, TKI resistance, caused by mutations in Bcr-Abl or aberrant activity of its network partners, remains a clinical problem. Using inducible expression and knockdown systems, we analyzed the role of Gab2 in Bcr-Abl signaling in human CML cells, especially with respect to TKI sensitivity. We show f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 52 publications
5
60
0
1
Order By: Relevance
“…7 However, based on experiences with other targeted therapy compounds such as imatinib or vemurafenib in CML 44 and melanoma, 42,45 respectively, it will be important to identify additional targets to identify synthetic lethal combinations by targeting 2 or more signaling hubs that are critical for tumor growth and survival, and to efficiently counteract the development of therapy resistance. Here, we report for the first time the functional significance and surface overexpression of the IGF1R protein and its baseline phosphorylation in human CLL cells ( Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…7 However, based on experiences with other targeted therapy compounds such as imatinib or vemurafenib in CML 44 and melanoma, 42,45 respectively, it will be important to identify additional targets to identify synthetic lethal combinations by targeting 2 or more signaling hubs that are critical for tumor growth and survival, and to efficiently counteract the development of therapy resistance. Here, we report for the first time the functional significance and surface overexpression of the IGF1R protein and its baseline phosphorylation in human CLL cells ( Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it is well demonstrated that BCR-ABL transformation requires PI3K-AKT signaling. [15][16][17][18][19][20][21][22][23][24][25] Furthermore, it was also shown that PIP3 levels are dramatically increased in CML. 26 Therefore, we hypothesized that PTEN could be functionally inactivated in the cytoplasm of CML cells.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, another study investigated the role of GAB2 overexpression in conferring resistance of CML cells to ABL1 TKIs and found that GAB2-mediated TKI resistance is also dependent on its interaction with SHP2 and p85. 50 Analysis of GAB2-dependent signals in BCR-ABL1-expressing primary myeloid and B-lymphoid cells revealed distinct roles for the GAB2 SHP2 and p85 binding sites in BCR-ABL1-induced transformation. In agreement with our previous observations, 16 AKT [53][54][55] We also discriminated the roles of SHP2 and PI3K binding to GAB2 in BCR-ABL1 signaling; whereas SHP2 binding is required for activation of ERK, S6, and STAT5, PI3K binding is required only for AKT activation.…”
Section: /2mentioning
confidence: 99%